EFEKTIVITAS MODEL PjBL BERBANTUAN LKPD TERHADAP KEMAMPUAN LITERASI MATEMATIKA SISWA SMK - Virgiano, M. Andre; Yensy B, Nurul Astuty; Haji, Saleh (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This study aimed to determine the effect of the Project Based Learning model assisted by Student Worksheets (LKPD) on the mathematical literacy skills of tenth-grade students at SMK Negeri 7 Rejang Lebong. The research method used in this study was a quantitative approach. The sampling technique used was purposive sampling. The research design used was a post-test-only control group design. In this study, the requirement was that both classes were homogeneous based on the number of students and the average grades of the odd semester final assessment for the 2023/2024 school year at SMK Negeri 7 Rejang Lebong. The test was conducted on statistics material, specifically the measures of central tendency of grouped data. The data collection technique was carried out through tests by providing a test instrument consisting of a set of questions. The test was given in the form of an essay. After conducting validity tests, reliability tests, discrimination index tests, and difficulty index tests, it would be determined whether the question items could be used, used but revised first, or not used. In this study, the t-test was used as the hypothesis test.